Identification of 2,2-Dimethylbutanoic Acid (HST5040), a Clinical Development Candidate for the Treatment of Propionic Acidemia and Methylmalonic Acidemia - Armstrong, Allison J; Henke, Brad R; Collado, Maria Sol; Taylor, Justin M; Pourtaheri, Taylor D; Dillberger, John E; Roper, Thomas D; Wamhoff, Brian R; Olson, Matthew W; Figler, Robert A; Hoang, Stephen A; Reardon, John E; et al. (Journal of medicinal chemistry, 2021)
Propionic acidemia (PA) and methylmalonic acidemia (MMA) are rare autosomal recessive disorders of propionyl-CoA (P-CoA) catabolism, caused by a deficiency in the enzymes P-CoA carboxylase and methylmalonyl-CoA (M-CoA) mutase, respectively. PA and MMA are classified as intoxication-type inborn errors of metabolism because the intramitochondrial accumulation of P-CoA, M-CoA, and other metabolites results in secondary inhibition of multiple pathways of intermediary metabolism, leading to organ dysfunction and failure. Herein, we describe the structure-activity relationships of a series of short-chain carboxylic acids which reduce disease-related metabolites in PA and MMA primary hepatocyte disease models. These studies culminated in the identification of 2,2-dimethylbutanoic acid ( , HST5040) as a clinical candidate for the treatment of PA and MMA. Additionally, we describe the in vitro and in vivo absorption, distribution, metabolism, and excretion profile of HST5040, data from preclinical studies, and the synthesis of the sodium salt of HST5040 for clinical trials.